Journey with nostos or without it. Many faces of the Homeric hero, Odysseus - Tuszyńska, Krystyna (Scripta Neophilologica Posnaniensia, 2020)
Odysseus or in Latin, Ulysses, is kind of literary character who, by his special qualities and his adventures, gives writers many possibilities of variation in reworking the myth. The demand of the audience as well as the authors’ desire for originality provide the main motive of the myth to be presented in a new way. Thanks to it, every writer, who undertakes a piece of work, tries to produce a new portrait of the well-known mythical hero. The source of variation in the myth can also be the natural tendency of authors to assimilate the old material to contemporary fashions and customs1. Problems of morality must have also arisen in the development of the myth over the centuries. Another cause of change in the traditional material lies in the writer’s technical inventions. All of these factors are interesting enough to the present author in presenting the many faces of the Homeric hero, Odysseus, which have changed over the course of time.